ACADEMIC ENGLISH VERBS ACROSS FIVE DISCIPLINES IN SOCIAL AND HUMANITIES: EVIDENCE FROM CORPUS - Gusti Ayu Praminatih (E-Journal of Cultural Studies, 2024)
Corpus provides a significant amount of data that can be utilised to retrieve actual language use, especially for teaching English for academic purposes. Accordingly, exploring academic English verbs (AEVs) across five disciplines, i.e., tourism, business, linguistics, management, and cultural studies, is essential. Further, it is also crucial to compare AEVs against Coxhead’s Academic Word List (AWL). A personalised corpus was built from 100 Scopus-indexed paper abstracts to achieve these objectives. Subsequently, the AntConc software was employed to retrieve AEVs. The study discovered that the top 50 AEVs varied across five disciplines and had similarities and differences, representing the characteristics and uniqueness of each field of study. The AEVs generated from the established corpus also appeared in Coxhead’s AWL. Consequently, the findings generated by this study are worth teaching, especially to EFL students, to robust the richness of verbs for academic purposes. Consequently, pedagogical implications are also described further in this study. Keywords: academic article abstracts, academic English verbs, corpus linguistics, English for academic purposes